1984
DOI: 10.1002/for.3980030204
|View full text |Cite
|
Sign up to set email alerts
|

Using the life cycle to anticipate satisfaction at work

Abstract: It was hypothesized that there are important non-linear life-cycle influences upon job and organizational satisfaction. Five common lifecycle stages were identified from the literature: the phases of 'reality shock', 'socialization and growth', 'mid-career crisis', 'acceptance', and 'pre-retirement'. The first, third and last stages were expected to show declines in job and organizational satisfaction because of the personal and job-related disappointments and crises that typically occur during these periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Other research has shown that job satisfaction varies with age. Kets de Vries, Miller, Toulouse, Friesen, Boivert, and Theriault (1984) found that job satisfaction declined during a person's 20s, it peaked during the late 30's or early 40's, and finally job satisfaction declined as the retirement age approached. In an international study of age and job satisfaction, it was found that satisfaction was at it lowest point at the age of 25 to 31, but satisfaction increased each year until a worker's career was completed (Birdi, Warr, & Oswald, 1995).…”
Section: Agementioning
confidence: 99%
“…Other research has shown that job satisfaction varies with age. Kets de Vries, Miller, Toulouse, Friesen, Boivert, and Theriault (1984) found that job satisfaction declined during a person's 20s, it peaked during the late 30's or early 40's, and finally job satisfaction declined as the retirement age approached. In an international study of age and job satisfaction, it was found that satisfaction was at it lowest point at the age of 25 to 31, but satisfaction increased each year until a worker's career was completed (Birdi, Warr, & Oswald, 1995).…”
Section: Agementioning
confidence: 99%
“…Although well-being in the workplace setting has been thoroughly examined, the notion of overall employee well-being (beyond only while at work) has been established only recently (Zheng et al 2015;Węziak-Białowolska, McNeely, and Vanderweele 2019). Further, well-being in the work setting is usually conceptualized through the lens of a single life-related measure, such as mental health/depression (Sanne et al 2005;Stansfeld et al 2012;Bentley et al 2015;Saijo et al 2015;Madsen et al 2017), the life satisfaction-job satisfaction link (Diener and Tay 2017;Near and Sorcinelli 1986;Rice, Near, and Hunt 1980), workplace friendship (Sias and Cahill 1998;Morrison and Cooper-Thomas 2016), and work motivation and the life cycle (Kets De Vries et al 1984), while disregarding the complex multidimensional links between well-being in the workplace, work outcomes, job resources, job demands and resources in life.…”
Section: Worker Well-beingmentioning
confidence: 99%